"The pain of the negative": The formulation of the philosophical spirit in the prologue to the Phenomenology of the Spirit - Rendón, Carlos Emel (Estudios de Filosofía, 1997)
The author holds that the Bildung of philosophical mind, as it is developed in the Foreword to the Phenomenology, is an appeal to make the effort ofconcept. This thesis is elaborated in two steps. First of all, it is pointed out that it is necessary to set up an immanent relation to the object, i.e., to express the necessity of its movement, in sofar as Hegel thinks of the object of Phiiosophy and its notion as being closely bound to life. Hence, Hegel's philosophy constitutes a sound criticism to Kantianformalism. Second, Hegel regards Philosophy as a work whose main experience is alienation (Entfremdung), and that it expresses thefinite character that distinguishes human rationality. From the latter statement, Hegel starts a criticism, on the one hand, to the enthusiasm proper to Romanticism and, on the other one, to intuition as a sudden understanding of whatever exists.